2022
DOI: 10.1039/d2ma00670g
|View full text |Cite
|
Sign up to set email alerts
|

White light emission generated by two stacking patterns of a single organic molecular crystal

Abstract: Dual emission by monomers and excimers is expected for single-molecule white light emitters. However, in the case of a system with an ideal excimer in a single conformation, it is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Since the SCXRD experiments were accomplished for only one single crystal and considering that the dye is incorporated as a dopant in the material, it is not expected to observe a clear tendency/relationship between the amount of AO included in the material and the effect on the lattice parameters. Nevertheless, for all samples, the trend is the same: an expansion in a and a shrinkage in b and c (difference in %, average: +0.150 (6), −0.370 (14), and −0.070(2), respectively). These results could be associated with a differential effect in each direction of the crystal when the dye (guest) is incorporated in the guaninium chloride (host).…”
Section: Synthesis Of Guanine-based Crystalline Materialsmentioning
confidence: 89%
See 1 more Smart Citation
“…Since the SCXRD experiments were accomplished for only one single crystal and considering that the dye is incorporated as a dopant in the material, it is not expected to observe a clear tendency/relationship between the amount of AO included in the material and the effect on the lattice parameters. Nevertheless, for all samples, the trend is the same: an expansion in a and a shrinkage in b and c (difference in %, average: +0.150 (6), −0.370 (14), and −0.070(2), respectively). These results could be associated with a differential effect in each direction of the crystal when the dye (guest) is incorporated in the guaninium chloride (host).…”
Section: Synthesis Of Guanine-based Crystalline Materialsmentioning
confidence: 89%
“…Organic single crystals are a class of materials that have useful properties such as optical/optoelectronic applications. Among others, they can act as optical waveguides, solid lasers, , and light-emitting diodes. In addition, mechanical properties such as flexibility provide another design dimension of the material extending the range of potential applications. , In an effort to rationalize crystal engineering tools for the design of new organic solids with specific mechanical properties, and having into consideration that those are linked to the degree of isotropy/anisotropy in the crystalline packing, Reddy and Desiraju and co-workers, demonstrated that the resultant behavior of the material can be controlled by modulating the strength and directionality of the intermolecular interactions; these include hydrogen and halogen bonding and π···π and C–H···π interactions . Recently, organic single crystals with both elastic bending ability and optical/optoelectronic functions (represented sometimes by the acronym EOSCs: Elastic Organic Single Crystals) have attracted increased attention. , Since the first reports, new types of elastic single crystals were discovered; they include doped systems, flexible metal–organic coordination compounds and biogenic crystals, , and even an example of an organic salt biocrystal such as clofazimine hydrochloride .…”
Section: Introductionmentioning
confidence: 99%
“…Under irradiation, DAEs can undergo cyclization to 4a,4b-dihydrophenanthrene derivatives (Scheme 1A) [8] that are easily oxidized to the corresponding phenanthrene derivatives. This reaction is applied in the synthesis of phenanthrenes, their heterocyclic analogs and advanced polyaromatics, [9][10][11] helicenes, [12,13] nanographenes and nanoribbons. [14,15] Photocyclization of VBAs is used in the synthesis of 9,10-dihydrophenanthrenes and their derivatives, [16,17] including natural products.…”
Section: Introductionmentioning
confidence: 99%